Planting Density and Dose of Nitrogen and Potassium as Influencing Pod Characters of Snap Bean (Phaseolus vulgaris L.) - Abdalla Mohamed Hussein; Mebrouk Benmoussa (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study is to investigate the planting density, nitrogen and potassium influencing on the pod characteristics of bean. The experiment is made in a Split Randomized Complete Block Design, replicated three times. Two plant densities and seven doses of nitrogen and potassium fertilizers were examined. The results reflected that density had no effect on pod attributes, except pod length in the second season, whereas significantly increased by the lower density. The plant received lower nitrogen lacking potassium increased length in the both seasons however, the higher individual potassium dose and control increased length in first and second seasons, respectively. The widest and narrowest pod diameters shown by the lower dose of nitrogen and higher dose of both fertilizers, subsequently. The separately maximum and minimum dose of potassium in the first and second season subsequently, in addition to the individual lower dose of nitrogen in the second season have a heaviest dry weight. The interaction significantly affected overall parameters, except pod diameter and dry matter in the first season. Pod dry matter is commonly constant, except with the higher density received the greatest dose of both fertilizers, whereas record significant decline. Pod length and diameter are good indicator of quality, it can be given by the lower density and lower dose of nitrogen without potassium. The combination between lower density with higher potassium dose or neutral dose of both fertilizers is a preferable for length while, the higher density with both doses of potassium or with lower nitrogen, is an appropriate for diameter. The best treatment for both, dry weight and dry matter are wobbly.